REVITALISASI DAN MODERENISASI POTENSI DESA BERBASIS INTEGRATED TOURISM DI ERA PANDEMI COVID-19 - Mulyono, Galih; Gianov Woda Niki, Leonardo; Martinus Rianu, Bagas; Angelitta Susanto, Precilia; Devika, Mutiara (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2022)
Rural development is the basic strength of a country. Equitable development is a priority program from the government that has been adapted to laws and regulations as an embodiment of the spirit to protect constitutional rights, for the welfare of all Indonesian people. In the research of the Village Empowerment Program (P3D) in Tumpang Village in 2021, Tumpang Village has the potential for Livestock, Processed Food Products, and Tourism. The village development program aims to create integration towards a modernization system in improving the quality of human resources in Tumpang Village comprehensively. The form of participation and active role of the community to build the village into an independent tourist village. The synergy between the motivation of the target villages and the program implementation objectives by the P3D team at Merdeka University Malang is then realized in a program scheme that is expected to be carried out in a sustainable manner. The scheme for village tourism activities that support the concept of integrated tourism is educational tourism, exploration, cultural tourism, and ecotourism.